2018
DOI: 10.5337/2018.221
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the nutrition and water targets of the Sustainable Development Goals: achieving progress through linked interventions

Abstract: The CGIAR Research Program on Water, Land and Ecosystems (WLE) is a global research-for-development program connecting partners to deliver sustainable agriculture solutions that enhance our natural resources-and the lives of people that rely on them. WLE brings together 11 CGIAR centers, the Food and Agriculture Organization of the United Nations (FAO), the RUAF Foundation, and national, regional and international partners to deliver solutions that change agriculture from a driver of environmental degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…However, a trial from Bangladeshwith similar intervention arms as the study in Kenyareported reduction in diarrhea in all intervention arms, except the intervention arm receiving water treatment only [17]. Although some of these recent studies have reported no effect of the interventions tested, the benefits of WASH for diarrheal diseases and other health outcomes should not be underestimated [37,38]. The findings may also not be generalizable across all contexts and therefore should be viewed in light of the specific interventions and setting [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, a trial from Bangladeshwith similar intervention arms as the study in Kenyareported reduction in diarrhea in all intervention arms, except the intervention arm receiving water treatment only [17]. Although some of these recent studies have reported no effect of the interventions tested, the benefits of WASH for diarrheal diseases and other health outcomes should not be underestimated [37,38]. The findings may also not be generalizable across all contexts and therefore should be viewed in light of the specific interventions and setting [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the scale permits comparative studies that quantify the multiple components of water insecurity with higher resolution than currently possible, allowing for the identification of global inequities, as well as vulnerable sub-populations within communities. The scale also has the potential to identify determinants of water insecurity and assess the health, economic and psychosocial consequences of household water insecurity, including food insecurity 36. Furthermore, the scale could be used to monitor trends in water insecurity over time, such as how it is shaped by macro-level social, economic and political shifts; climatic variability; and local shocks, such as extreme weather events or contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Current global public health efforts could be more effective by addressing water and food insecurity jointly. For instance, there are Sustainable Development Goals for food and water, but none consider their many linkages; underappreciation of the interconnections between these 2 essential resources is significant given that improvements in one can be to the detriment of the other ( 2 ). Such delineations have contributed to disciplinary siloing, although coordination between the WaSH and nutrition sectors is needed to advance the goals of each ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greater agricultural yields can increase a household's income, allowing individuals to purchase more (diverse) food ( 112 ). Further, irrigation technologies that produce clean water (e.g., desalination) can function as multiple-use water systems, meaning individuals can use the expanded water supply for other household needs, like water, sanitation, and hygiene (WaSH) activities that ensure the safe handling and preparation of foods ( 2 ). Another potential mechanism of action is through expanded women's empowerment.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation